Review Essay. (March 2013) - Kourula, Arno
This review essay addresses first the author's own assessment of the United Nations Global Compact (UNGC) and second the structure and contribution of the book edited by Andreas Rasche and Georg Kell on The United Nations Global Compact: Achievements, Trends and Challenges (Cambridge, UK: Cambridge University Press, 2010). The book brings together contributions by academics and practitioners from business, civil society, and the UNGC office.